1999
DOI: 10.1177/00220345990780010201
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Gene Expression in Epithelial Cells of Mixed Odontogenic Tumors

Abstract: Comparative investigations of odontogenic cells in normally forming teeth and tumors may provide insights into the mechanisms of the differentiation process. The present study is devoted to late phenotypic markers of ameloblast and odontoblast cells, i.e., proteins involved in biomineralization. The in situ expression of amelogenins, keratins, collagens type III and IV, vimentin, fibronectin, osteonectin, and osteocalcin was performed on normal and tumor odontogenic human cells. The pattern of protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 78 publications
(74 reference statements)
0
50
0
12
Order By: Relevance
“…Only a small number of AFOs have been submitted to molecular and genetic studies but no significant findings have been found thus far that can contribute to our knowledge of the biological behavior of this lesion [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of AFOs have been submitted to molecular and genetic studies but no significant findings have been found thus far that can contribute to our knowledge of the biological behavior of this lesion [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin has been detected in various mesenchymal cells types of the tooth organ, including odontoblasts (Lyn et al 1991;Seux et al 1991;Inoue et al 1992;Lombardi et al 1992a;Davidson 1994;Papagerakis et al 1999). The fact that we were unable to detect its presence in odontoblasts by high-resolution immunocytochemistry may be due to denaturation of antigenic sites during tissue processing and/or to its presence in amounts that are below the detectability threshold of Figure 1 Electron micrograph of rat incisor presecretory stage ameloblasts (PS-Am) at a position where they show short cytoplasmic processes (asterisks) extending into the forming mantle predentin.…”
Section: Discussionmentioning
confidence: 99%
“…In osteopetrotic (op/op) mice, incisor tooth germ could not erupt, but odontoma tissues are formed in the root apex instead due to the invasion of alveolar bone trabecular 9,10 . Owing to lack of some tooth eruption requirements, especially the osteoclastic induction factors 10 , one of the most intensively studied factors is macrophage colony-stimulating factor (M-CSF).…”
Section: Evidencesmentioning
confidence: 99%